ANALYSIS OF VALUE-ECONOMIC CHARACTERISTICS OF INTROGRESSIVE HYBRIDS OF COTTON UNDER DIFFERENT SOIL-CLIMATE CONDITIONS IN UZBEKISTAN - Juraev S. T.; Yakubjonova N. A. (Galaxy International Interdisciplinary Research Journal, 2022)
In the introgressive hybrids of cotton, the possibility of adaptation of valuable economic characters, the influence of genotype and environment, their interdependence on yield and other valuable economic characters, creation of new highly adaptable varieties is of great importance. In order to determine the effect of genotype and environment on character expression and their interaction, a two-factor dispersion analysis was conducted in F2-F4 hybrid combinations for economic characters. According to the obtained results, the heritability of productivity is low and it can be positively influenced by various external factors. As a result of conducting selections for three years, an increase in the yield of hybrid combinations was achieved on average by 10.5 t/ha. Two-factor dispersion analysis showed that the influence of the genotype on the variability of the duration of the growing season in F2-F4 hybrids over the years was insignificant, the contribution of the environment was 68.3%, and the contribution of the genotype-environment was 19.0%. Based on the results of dispersion analysis, it was found that the genotype and environmental factors had a joint effect on the fiber yield characteristics of the hybrids at the same time. In this case, the influence of the genotype was much higher, 40.1%, and the influence of the environmental factor was equal to 12.6%.